2013
DOI: 10.1021/jp4053874
|View full text |Cite
|
Sign up to set email alerts
|

Host–Guest Chemistry from Solution to the Gas Phase: An Essential Role of Direct Interaction with Water for High-Affinity Binding of Cucurbit[n]urils

Abstract: An investigation of the host–guest chemistry of cucurbit[n]uril (CB[n], n = 6 and 7) with α,ω-alkyldiammonium guests (H2N(CH2) x NH2, x = 4, 6, 8, 10, and 12) both in solution and in the gas phase elucidates their intrinsic host–guest properties and the contribution of solvent water. Isothermal titration calorimetry and nuclear magnetic resonance measurements indicate that all alkyldiammonium cations have inclusion interactions with CB[n] except for the CB[7]–tetramethylenediamine complex in aqueous solution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 64 publications
3
53
0
Order By: Relevance
“…To date, the highest binding constants have been achieved using macrocyclic cucurbituril molecules as host systems. 68 Alternative approaches based on synthetic cyclophane systems have the potential advantage that the binding partners can be optically or redox active, 9-12 but they are presently limited by relatively weak association constants in water. 13,14 Recently, we discovered an unusually effective supramolecular process that threaded a tetralactam macrocycle onto a fluorescent squaraine dye (Scheme 1) that was flanked by two long polyethylene glycol (PEG) chains.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the highest binding constants have been achieved using macrocyclic cucurbituril molecules as host systems. 68 Alternative approaches based on synthetic cyclophane systems have the potential advantage that the binding partners can be optically or redox active, 9-12 but they are presently limited by relatively weak association constants in water. 13,14 Recently, we discovered an unusually effective supramolecular process that threaded a tetralactam macrocycle onto a fluorescent squaraine dye (Scheme 1) that was flanked by two long polyethylene glycol (PEG) chains.…”
Section: Introductionmentioning
confidence: 99%
“…Anumber of studies have reported distinctive host-guest chemistries in the gas phase that are unseen in solution. [3,5] Notably,r emoval of solvent was found to enhance noncovalent interactions and drive complexation. [3,5a] Utilizing this characteristic,w ei nvestigated the complexes of monosaccharide isomers and as ynthetic host in the gas phase to examine their intrinsic binding properties in the absence of solvation effects.M onosaccharides are the most common neutral hydrophilic biomolecules,b ut artificial recognition systems effectively targeting them are limited.…”
mentioning
confidence: 99%
“…The stability constants ( K ) for the complexation of the guests 2 + and 4 2+ with TMeQ[6] are much higher than those measured for the same guests with the parent Q[6]29. The large K values change is most probably due to the enhancement of host–guest interactions, including ion-dipole and van der Waals interactions.…”
Section: Resultsmentioning
confidence: 99%
“…As a class of organic cyclic oligomers, Q[ n ]s possess a hydrophobic cavity and two identical carbonyl-laced portals that can bind with all kinds of organic molecules to form inclusion complexes. For example, Q[6] has been shown to form rotaxane and pseudorotaxane constructs with a variety of alkylammonium and alkyldiammonium ions272829303132. Q[7] exhibits excellent binding affinity to amantadine and ferrocene derivatives33.…”
mentioning
confidence: 99%